If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (72.62x) + (1.26a) + -1(2844x + -8.23a) = 0 Reorder the terms: (72.62x) + (1.26a) + -1(-8.23a + 2844x) = 0 (72.62x) + (1.26a) + (-8.23a * -1 + 2844x * -1) = 0 (72.62x) + (1.26a) + (8.23a + -2844x) = 0 Reorder the terms: (1.26a) + 8.23a + (72.62x) + -2844x = 0 Combine like terms: (1.26a) + 8.23a = 9.49a 9.49a + (72.62x) + -2844x = 0 Combine like terms: (72.62x) + -2844x = -2771.38x 9.49a + -2771.38x = 0 Solving 9.49a + -2771.38x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2771.38x' to each side of the equation. 9.49a + -2771.38x + 2771.38x = 0 + 2771.38x Combine like terms: -2771.38x + 2771.38x = 0.00 9.49a + 0.00 = 0 + 2771.38x 9.49a = 0 + 2771.38x Remove the zero: 9.49a = 2771.38x Divide each side by '9.49'. a = 292.0316122x Simplifying a = 292.0316122x
| 8(2x-9)=2(8x+6) | | 3x^3=32 | | 9+11z-3=5z+69-3z | | -3(x-1)-7=4x-11 | | 18+3y=9y | | (24.2x)+(8.25)+(83.6x-2.92)= | | 4x=28-0.25(4-16x) | | 5n-6(n+2)=14 | | -8(3x-4)+1=15 | | 5s+3s=56 | | (2x+6a)-(4x-a)= | | 8x=14-0.5(10x+2) | | 2z=-10 | | 61=16+5(x-3) | | 4.2q-5.9-5.5q=-2.3q-3.6 | | 8p=2(p+9) | | 8(w-2)= | | 100.39=28.90+49.99+2x | | (2x+5)+(x-2)= | | a+(a+450000)=625000000 | | 38.5=2x-1.5+2x-1.5+x+x+x+7.2 | | 33.9ab-82.4ac+29.3ad-84.8ac+73.2ab= | | y-17=-33 | | 2x-20=36.37 | | 9.9x+38.57=-10.1+38.41b | | 108=x+x+3.5x+3.5x | | Y^2+2y-24=0 | | 66.8=2x+4.7+2x+4.7+2x+4.7+2x+4.7 | | (c-3)(c-3)=o | | x+4=9x-72 | | 9(3+x)= | | 27y^2-52y+25= |